GAYA SILINDER STICK DAN SILINDER BUCKET PADA EXCAVATOR 320 CATERPILLAR AKIBAT GAYA POTONG - Zuchry, Muhammad (Jurnal MEKANIKAL, 2012)
The use of heavy equipment to help physical work is very much in use today, One of them is the Excavator. CAT 320 Excavator jeis has many advantages in using, is evident from the construction equipment, design and engineering technology used. In the design of the machine is certainly not independent of the condition of fuel-efficient, compact and easy operation in sistym.Excavato CAT 320 is equipped to do the job of supporting the boom, stick and bucket. Stick used in the job can be changed according to the type of work to be done. Type of stick used is the type R B 1.9, R 2.5 B, R B 2.9, R 3.9 B, M 1, 9 C, M2.4 C, and M 2.9 B and is tailored to the lift cylinder to be used. The length of each stick is 1900 mm, 2400 mm, 250 mm, 2920 mm, 3860 mm. While the bucket capacity (0.7 to 1.2) m3. With the use of the stick and bucket will be analyzed style stick and bucket cylinder and the diameter of the stick and bucket.